Small bowel obstruction with multiple perforations post chestnut ingestion. Issue 2 (3rd February 2019) - Ravindra, Raevin K; Das, Atandrila; Chew, Grace L; Daniel, Eric
Abstract : Phytobezoars are a rare cause of small bowel obstruction (SBO), which consists of vegetable matter such as seeds, skins, fibres of fruit and vegetables that have solidified. We present the case of a 61-year-old man with no previous surgery who presented with central abdominal pain, nausea and vomiting. An abdominal CT scan demonstrated SBO with a transition point in the left anterior abdomen. He proceeded to a laparoscopy, which revealed multiple perforations throughout the small bowel, from the proximal jejunum to the terminal ileum. Laparotomy was performed, and undigested chestnuts were milked out through the largest perforation and the perforations were oversewn. While obstruction due to phytobezoars is rare, this case demonstrates the importance of considering small bowel trauma and perforation due to phytobezoars and highlights the need for close inspection of the entire gastrointestinal tract for complications in the setting of phytobezoar-related bowel obstruction.